Relationship between attitudes, beliefs, feelings of violence in Tamil films and violent behaviour among Indian teenagers - Munusamy, Kalaivani (2016)
Television contains a wealth of movie genres that can be one of the potential contributors to the growth of violent behavior among teenagers. Violent film is one of the issues that is gaining wide attention from the electronic media. Thus, violence in films is one of the specific learning conditions believed to be a potential contributor towards the growth of violent behaviour among teenagers. According to Natesan (2012), Tamil films on television are prime examples that promote and spread gangsterism among the Indians. From previous research, violent behaviour problems among teenagers and the effect of viewing violence in media have already existed in Malaysia. This leads to high crime rate among Indian teenagers. The general objective of this study is to examine the relationship between viewing violent scenes in Tamil films on television towards the behaviours of Indian teenagers. Apart from that, it specifically focuses on the pattern of watching films on television among Indian teenagers, the relationship between attitudes of viewing violent scenes in Tamil films and the behaviours of Indian teenagers, the relationship between beliefs in viewing violent scenes in Tamil films and the behaviours of Indian teenagers; and also the relationship between feelings of viewing violent scenes in Tamil films and the behaviour of Indian teenagers. A quantitative method was used in this study. Two sampling methods were employed in this study. The sample of this study consisted of 400 teenagers from a total population of 133, 767 Indian teenagers in Selangor. The sampling methods were convenient sampling and purposive sampling. This location was selected for the study because data showed that the state has the highest crime rates. The study was designed based on the Cultivation Theory.The data was analysed using Statistical Package for Social Sciences (SPSS) version 22.0. Descriptive statistic and inferential statistic were used in this study. Descriptive statistic was used to identify percentage values, mean, average and standard deviation. While inferential statistic was used to explain the relationships that contribute to the variables of the study. Teenagers who involved in this study spent a considerable amount of time to watch television and specially watch Tamil films on television in a week more than 13 times. Thus, almost more than half of respondents spent more than three hour to watch Tamil films in a day and like to watch films on television on Sunday. The correlation result showed that there is a strong relationship between attitudes of watching violent scenes in Tamil films and Indian teenagers’ behaviour (0.832), beliefs of watching violent scenes in Tamil films and Indian teenagers’ behaviour (0.908) and feelings of watching violent scenes in Tamil films and Indian teenagers’ behaviour (0.939). The correlation was significant at 1% level of significance. The results revealed that teenagers give positive reactions towards violence in Tamil films on attitudes; beliefs and feelings that enhance their changes of violent behaviours. In today’s world, exposure to violence is essentially unavoidable. Teenagers tend to be affected negatively from the violence in films and follow sensational stories created by the media for profit purpose. Therefore, it is very important for the film censorship board to filter out violent scenes in Tamil films before telecasting them in the television. This is because there is lack of awareness on the violent messages that are steadily instilled in young viewers’ minds, and the moral values that defied their development.